HOLOGRAPHIC TEACHER: STRATEGIES FOR ENHANCING THE EFFICIENCY AND ENGAGEMENT POTENTIAL OF PROGRAMMING STUDENTS THROUGH UNREAL ENGINE AND AI (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article presents a comparative analysis of the impact of using holographic technologies in higher education—particularly in Programming and IT fields—on learning effectiveness and student engagement. The study examines the advantages of holograms over traditional teaching methods, especially in enhancing spatial thinking and visualizing complex abstract concepts. The paper also explores in detail the use of Unreal Engine to create highly interactive and realistic content, as well as strategies for integrating artificial intelligence platforms such as ConvAI to transform holograms from static visual tools into dynamic, real-time interactive “intelligent tutor” agents. Additionally, real-time performance (low-latency) requirements, technical limitations, and issues of academic integrity are analyzed, and practical recommendations are provided for implementing holographic solutions in the IT domain.
Keywords: Holographic technologies, Higher education, Learning effectiveness, Student engagement, Unreal Engine, ConvAI, Artificial intelligence (AI), Real-time processing, Interactivity, Programming education, IT education, Immersive learning, Virtual instructors.